Assessment of metal pollution using enrichment factor (EF) and pollution load index (PLI) in sediments of selected Terengganu rivers, Malaysia - Nor Sayzwani Sukri; Siti Amirah Aspin; Nurul Liyana Kamarulzaman; Nurul Fazlina Jaafar; Rozidaini Mohd Ghazi; Nor Shahida Shafiee @ Ismail; Siti Hajar Yaacob; Farah Khaliz Kedri; Mohamad Pauzi Zakaria
Anthropogenic activities that happen in Terengganu River were contributed to sediment pollution at that area. The sediment pollution occurred when sediment are additional influenced with chemical adsorption between the metals, grain size, and organic matter. Thus, this study was conducted to assess the metal pollution using Enrichment Factor (EF) and Pollution Load Index (PLI) and compared with the previous study. A total of 15 sediment samples were collected from 5 different rives and metal concentration were analyzed using flame Atomic Absorption Spectrometer (ASS). The metal concentration ranged as followed: Cr (0.48-12.80 mg/kg), Cu (0.38-15.20 mg/kg), Mg (202.00-2769.00mg/kg), K (63.36-1730.00 mg/kg), Mn (4.27-33.70 mg/kg), Zn (2.05-31.30 mg/kg) and Cl (141.00-584.00 mg/kg) respectively. Enrichment Factor (EF) and Pollution Load Index (PLI) were used as a pollution indicator to access the sediment pollution in selected Terengganu Rivers. The mean Enrichment Factor (EF) value indicated in decrease order Cl (34.70) > Zn (23.44) > Cu (10.37) > Cr (1.95) > K (1.58) > Mg (1.16)> Mn (0.87). Meanwhile, Pollution Load Index (PLI) value showed below than 1 in all sampling stations. When compared with previous study, Mg and Cl metals need to take further action due to dramatically increased within seven years. The output from this study will be useful for environmental management at Terengganu Rivers.